(untitled) - Kinney, Michael R. (Victoria, 2006)
The most practical, real-world presentation of cost accounting on the market, this book blends a traditional and proven method of teaching cost accounting with the integration of innovative topics. Cost topics are covered in the context of organizational strategy and operational tactics, as cost management decisions are sensitive to strategies driven by quality, cost, and innovation. Kinney, Prather-Kinsey, and Raiborn reinforce the material with real-world examples and visual illustrations that bring cost management techniques into the student's sphere of understanding. A flexible organization appropriate for either a one- or two- semester course--coupled with clear and abundant visual presentations--allows students to clearly understand difficult topics. The text's revised organizational structure streamlines chapter materials as well as reduces redundancy between cost accounting and other business courses.
Keywords: Cost accounting,Managerial accounting